A longitudinal study of immunization status and reasons for non-vaccination of children in OPD and pediatric ward of a teaching hospital - Khurram, Mir Sumsam Ali; Khan, Khaja Amer (International Journal of Contemporary Pediatrics, 2020)
Background: The present study was to find out the immunization status of children in the age group of 0-7 years from OPD and those admitted in hospital attached to Deccan College of Medical Sciences with respect to primary immunization (BCG,OPV/DPT 1, 2, 3, measles), 1st booster dosage of OPV, DPT and also primary doses of Hepatits-B vaccine and coverage of vitamin A with measles vaccine. The objectives of this research work were to study factors which influence the immunization status and to know reasons for partial and non-immunization and their follow up over 2 years. Also, to know proportion of vaccine preventable diseases in children under study group. Methods: An oral questionaire method was adopted for parent of children in the age group 0-7 years to assess their immunization status and social factors influencing immunization coverage. Systemic random sampling method was applied to select 200 chlildren i.e. every 5th child admitted in the age group of 0-7 years was taken for analysis. Results: The study showed that out of 200 children 115 were fully immunized, 78 were partially immunized and 7 were non- immunized, 66 children among male and 49 among females were fully immunized, & the study shows that males had better immunization than females. Conclusions: Out of total 200 cases 57.6% were fully immunized, 38 % were partially immunized while 3.5% were unimmunized. Immunization coverage was better in urban children than rural children.